Penggunaan Metode Hybrid e-Learning untuk Praktikum Imunologi Farmasi di Fakultas Farmasi Universitas Gadjah Mada - Ikawati, Muthi'; Hermawan, Adam; Sahid, Muhammad Novrizal Abdi; Kristina, Susi Ari; Sasmito, Ediati (Jurnal Kefarmasian Indonesia, 2021)
Laboratory work of Pharmaceutical Immunology, Faculty of Pharmacy UGM aims to provide skills of applying antigens, antibodies, and immunological techniques in pharmaceutical; and ideally each student should be able to perform it completely. However, the limitation of time and facilities making the learning process ineffective. An innovative learning method such as hybrid e-learning is expected to increase the learning effectiveness. Learning materials and online quizzes/discussions were uploaded and carried out using elisa.ugm.ac.id (eLisa), respectively, combined with on-site works in the laboratory. The method was evaluated by examination scores and final grades. Student participations in online quizzes increased from first to fourth quiz (average participation rate 98.86±0.87%). Compared to the conventional method applied in 2016 (n=207), the examination average score did not increase; however, the percentage of students whose score is 90-100 were higher in the hybrid e-learning. The average final grade of the hybrid e-learning was 81.43±0.70; whereas the conventional method of 2016 was 80.22±5.22. More than 80% students (n=48) expressed easiness in following courses and were satisfied with the online learning materials’ quality. Hence, the hybrid e-learning results positive effects in increasing the effectiveness of the learning process. Development of more interactive online platforms is needed to optimize the learning process.